First-principles study of CO adsorption on Os atom doped anatase TiO2 (1 0 1) surface. (15th November 2020) - Lin, Long; Shi, Zhengguang; Yan, Longbin; Tao, Hualong; Yao, Linwei; Li, Shaofei; Xie, Kun; Huang, Jingtao; Zhang, Zhanying
Graphical abstract: The adsorption mechanism of CO on anatase TiO2 (1 0 1) modified surface was studied using the first-principles based on density functional theory. The results showed that oxygen vacancy modification and oxygen vacancy and noble metal Os atom-doped co-modification could enhance its adsorption performance. Highlights: The adsorption behavior of CO on pure TiO2 and its modified surface was studied theoretically. Both oxygen vacancy modified surface and noble metal Os doped surface can increase the adsorption stability of CO. It provides a theoretical basis for the design of CO gas sensor. Abstract: In this paper, the adsorption of CO on the three anatase TiO2 (1 0 1) surface systems of intrinsic TiO2, an oxygen vacancy modification (VO /TiO2 ), and co-modified by an oxygen vacancy and a doped noble metal atom Os (Os/TiO2 ) are studied by first-principles. The results show that the adsorption performance of CO on intrinsic TiO2 is fine; especially the adsorption performance is greatly improved after adding defects. The adsorption energies of the TiO2 system, the VO /TiO2 system, and the Os/TiO2 system are −0.552 eV, −1.591 eV, and −3.971 eV, respectively. By analyzing the adsorption energy ( ΔEads ), bond length, charge distribution, density of states (DOS) and charge differential density (CDD) of the three systems, it is found that their adsorption mechanism and adsorption methods are different. The intrinsic TiO2 system is physical adsorption, and the carbon atom in CO has a strong interaction with Ti5C, but they cannot form bonds. The VO /TiO2 system is chemical adsorption, and the carbon atom of CO exerts a strong interaction with Ti2, resulting in a C-Ti2 bond. The Os/TiO2 system is chemical adsorption, and the strong interaction between carbon atom of CO and OS atom causes the formation of C-Os bond.